Escherichia coli: a rare cause of meningitis in immuno-competent adult. Issue 1 (2nd January 2020) - Zafar, Maryam; Tauseef, Abubakar; Asghar, Muhammad Sohaib; Khan, Narmin; Farooqui, Nabeeha; Dawood, Mustafa; Alam, Tanvir; Naman, Durre
ABSTRACT: A 35-year-old male of Asian ethnicity presented with complaints of high-grade fever, severe headache, vomiting, generalized seizures, deteriorated conscious level and neck stiffness. After all baseline workup Computed Tomography (CT) scan of the brain was done, which turned out to be unremarkable. CT scan was then followed by lumbar puncture (LP) and Cerebrospinal fluid (CSF) detailed report was sent, which was highly suggestive of bacterial meningitis with the predominance of polymorphonuclear leukocytes. Later on, CSF culture and sensitivity report showed growth of Escherichia coli, which is one of the rare causes of meningitis in immunocompetent adults without any history of craniocerebral trauma, neurosurgical intervention, urinary or gastrointestinal tract infections, and an immunocompromised state. Abbreviations: CSF: Cerebrospinal fluid; LP: Lumbar puncture; CT: Computerized tomography; E-coli: Escherichia coli; GCS: Glasgow coma scale; COPD: Chronic Obstructive Pulmonary Disease; HTLV1: Human T-Lymphotropic virus −1; PCR: Polymerase chain reaction